Impairment of manual but not saccadic response inhibition following acute alcohol intoxication. (1st December 2017) - Campbell, Anne Eileen; Chambers, Christopher D.; Allen, Christopher P.G.; Hedge, Craig; Sumner, Petroc
Abstract: Background: Alcohol impairs response inhibition; however, it remains contested whether such impairments affect a general inhibition system, or whether affected inhibition systems are embedded in, and specific to, each response modality. Further, alcohol-induced impairments have not been disambiguated between proactive and reactive inhibition mechanisms, and nor have the contributions of action-updating impairments to behavioural 'inhibition' deficits been investigated. Methods: Forty Participants (25 female) completed both a manual and a saccadic stop-signal reaction time (SSRT) task before and after a 0.8 g/kg dose of alcohol and, on a separate day, before and after a placebo. Blocks in which participants were required to ignore the signal to stop or make an additional 'dual' response were included to obtain measures of proactive inhibition as well as updating of attention and action. Results: Alcohol increased manual but not saccadic SSRT. Proactive inhibition was weakly reduced by alcohol, but increases in the reaction times used to baseline this contrast prevent clear conclusions regarding response caution. Finally, alcohol also increased secondary dual response times of the dual task uniformly as a function of the delay between tasks, indicating an effect of alcohol on action-updating or execution. Conclusions: The modality-specific effects of alcohol favour the theory that response inhibition systems are embedded within response modalities, rather than there existing a general inhibition system. Concerning alcohol, saccadic control appears relatively more immune to disruption than manual control, even though alcohol affects saccadic latency and velocity. Within the manual domain, alcohol affects multiple types of action updating, not just inhibition.